The analysis of drug consumption, drug trafficking and the fight against drug trafficking at the present day - Borisenko M. V. (Interactive science, 2017)
the article discusses the current drug situation in Russia, Siberian Federal District and Novosibirsk Region relating to drug consumption and drug trafficking and the main reasons of deaths of drug-dependent people.
Keywords: преступления; crimes; производство наркотических средств; сбыт наркотических средств; незаконный оборот наркотиков; production of narcotic drugs; sale of narcotic drugs; drug trafficking